KONTRASTIVITAS INTERJEKSI BAHASA JEPANG DAN BAHASA BALI - Dwiyantari, Ni Kadek Ety (Humanis, 2014)
The title of this research is Kontrastivitas Interjeksi Bahasa Jepang dan Bahasa Bali. The discussion of this study is focused on the analysis of the comparison of Japanese interjection (kandoushi) and Balinese interjection (kruna pakeengan). The background of this topic is the existence of a word class in Japanese and Balinese that has the same expression of speaker emotional feelings called interjection. The purpose of this study is to understand the types and meaning of kandoushi and kruna pakeengan, as well as comparing both of them. The results of this study showed that there are similarities and differences between kandoushi and kruna pakeengan. The similarities between kandoushi and kruna pakeengan contain a variety of forms such as repetition, meaningful expression of emotional from the speakers whose meaning depends on the context of situation. In a sentence, interjection can work independently, and interjection can be abbreviated. The differences of kandoushi and kruna pakeengan are in the use of kondoushi there is level of politeness, greeting utterances, the utterance of agree or disagree toward the other person and the writing of punctuation kondushi in variety of language depends on the context of situation. Meanwhile, in the form of kruna pakeengan, the interjection of voice and the expression is more emphasis on the speaker command despite it was a noun, a verb, an adjective, or other word class.
Keywords: interjection, kandoushi, kruna pakeengan.